2020
DOI: 10.3390/su12051735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Nitrogen Addition on Wheat Yield, Nitrogen Use Efficiency, and Residual Soil Nitrate in a Semiarid Area of the Loess Plateau of China

Abstract: Nitrogen (N) fertilizer plays an important role in wheat yield, but N application rates vary greatly, and there is a lack of data to quantify the residual effects of N fertilization on soil N availability. A 17-yr experiment was conducted in a semiarid area of the Loess Plateau of China to assess the effects of N fertilization on spring wheat (Triticum aestivum L.) grain yield, N uptake, N utilization efficiency, and residual soil nitrate. Treatments included a non-N-fertilized control and annual application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 64 publications
7
30
0
Order By: Relevance
“…This is coherent because a large part of the additional N is driven to grain protein synthesis whereas yield increases were small (i.e., the concentration of N in the grain increases more than the yield). This result confirms previous reports made working with bread [33,39,43] and durum [44] wheat. Under both N treatments, high-yielding genotypes showed higher efficiency in the use of the applied N. This finding led us to hypothesize that NUE can be a trait under genetic control.…”
Section: A High Nitrogen Supply Increases Durum Wheat Grain Nitrogen supporting
confidence: 93%
“…This is coherent because a large part of the additional N is driven to grain protein synthesis whereas yield increases were small (i.e., the concentration of N in the grain increases more than the yield). This result confirms previous reports made working with bread [33,39,43] and durum [44] wheat. Under both N treatments, high-yielding genotypes showed higher efficiency in the use of the applied N. This finding led us to hypothesize that NUE can be a trait under genetic control.…”
Section: A High Nitrogen Supply Increases Durum Wheat Grain Nitrogen supporting
confidence: 93%
“…It has also been suggested that nitrate assimilation is suppressed under eCO 2 (Bloom et al, 2010). Nitrogen fertilizer application often improves wheat yield (Sudderth et al, 2005;Belete et al, 2018;Xu et al, 2020). We observed that greater N application rates significantly increased tiller number, aboveground dry biomass, leaf chlorophyll content and plant N content of wheat, in agreement with different studies on wheat and other plant species (Chaturvedi, 2005;Sudderth et al, 2005;Walker et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…From an exclusively economic point of view, it is estimated that a 1% improvement of N efficiency in cereals could save over US$200 million in N fertilizer costs, worldwide [71]. Therefore, fertilizing crops with excessive N rates not only poses environmental hazards, which is gradually becoming a serious cause for concern, but also leads to economic losses [44,54,[71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%